Determination of tensile strength of cementitious composites using fracture parameters of two-parameter model for concrete fracture - Ince, Ragip; Fenerli, Cenk (Elsevier Sci Ltd, 2022)
In this study, the formulation of the two-parameter model based on the size effect proposed by previous re-searchers was initially improved to be much more practical. Subsequently, six series of notched and unnotched beams with a size ratio of 1:4 and notched and unnotched square prismatic specimens with a size ratio of 1:6 were tested to verify this modified formulation. The peak loads obtained from the fracture tests of the notched specimens were examined using the two-parameter model. Then, the test results of the unnotched bending and splitting specimens were simulated according to the modified formulation. Furthermore, this formulation was applied to extensive test data obtained from the direct tension specimens with double edge notches and from the unnotched specimens in the literature to derive the direct tensile strength of concrete. Finally, when comparing the results of this study to the previous studies, there were slight differences among the other formulas, except for the one that covered splitting specimens.
Keywords: Beam test; Concrete; Fracture mechanics; Splitting test; Two-parameter model